Recent improvements in the Broadband seismic networks in Portugal - Caldeira, B. (2007)
Portugal, in spite of the significant earthquake region, (e.g.: Borges et al., 2001) has been operating a limited number of broadband digital seismic instruments. The older BB seismic station in a systematic and continuous operation on the country is MTE, belonging to GEOFON and locally supported by IM, which is working since 1997. To efficiently carry out the task of develop the Broadband Portuguese seismic network, there is a collaboration between some national institutions, such as Institute of Meteorology (IM), Geophysics Center of Évora University (CGE/UE), Geophysics Center of University of Lisbon (CGUL/IGIDL) and Instituto Superior Técnico (IST), with governmental support from the National Science and Technology Foundation (Rede Nacional de Geofísica, RNG). From this collaboration we expect shortly to assist the emergence of a high quality infrastructure, significant to real-time monitoring the earthquake activity for use by governmental authorities, and of paramount importance to scientific research. The installation of this network is to be carried out in narrow connection with international institutions as GEOFON, EMSC, ROA, ORFEUS, with who we saw to establish collaborations. Data from some stations are already being exported to international data centers, such as DMC and ORFEUS, and will be used for an upcoming prototype of an Early Warning Tsunami System to be developed for Cadiz Gulf coastal area and southwestern coasts of Portugal mainland, within the framework of the NEAREST project. Conclusions While the broadband network is developed they elapse investigation projects that request short period data. Of these projects we highlight the Seismic Tomography of the Continental Lithosphere of Algarve (Portugal) that involve the installation of a Portable seismic network consisting of 30 short- period stations, including a subnet of 7 telemetry stations, in operation since January 2006